Skyrmions and merons in two-dimensional antiferromagnetic systems. (March 2019) - Fernandes, R.L.; Lopes, R.J.C.; Pereira, A.R.
Abstract: We have investigated (numerically) skyrmions constituted by two merons in two-dimensional Heisenberg antiferromagnets. The behavior and stability of these topological pseudo-particles are analyzed in discrete and finite lattices. The influence of lattice defects and external magnetic fields is also studied. The topological stability dictates that the two merons must be kept apart but processes of annihilation and fusion of merons are observed for finite lattices. Highlights: The lattice finiteness impels an attraction between the merons, destroying the skyrmion texture. Skyrmions of type 2CS in the AFM lattice are more unstable than their counterparts in the FM lattice. A non-magnetic impurity next to the skyrmion 2CS attracts texture. A magnetic field parallel to the plane of the film can transform a 2CS skyrmion into type 1CS.